PENGEMBANGAN MEDIA UPIN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Cholidatul Izza; Tety Nur Cholifah (STKIP Persada Khatulistiwa Sintang, 2020)
The purpose of this research is to develop UPIN (Smart Ladder Snake) media products and to find out the improvement of student learning outcomes using UPIN (Smart Ladder Snake) media on the material of ethnic and religious diversity in my country in grade IV SD. The type of research used is research and development (R&D) with a model developed by Sugiyono. The research was carried out at SD Negeri 3 Sumbermanjing using the subject of 15 grade IV SD students for the 2019/2020 school year. The techniques and instruments used in this study were interviews, observations, questionnaires, tests, performance, documentation. Based on the results of the research conducted, the following conclusions were obtained. Learning outcomes using 3_realm that is cognitive aspects with a percentage increase in learning outcomes of Indonesian language learning content by 60% while science subject content is 60%, affective aspects with a percentage increase in learning outcomes by 83%, psychomotor aspectswith a percentage increase in learning outcomes by 60%. Thus it can be concluded that the UPIN (Smart Ladder Snake) media on the material of ethnic and religious diversity in my country in grade IV SD can improve student learning outcomes.